New compact and noncompact solutions of the K(k,n) equations - İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2006)
In this paper, we establish exact solutions for the K(k, n) equations. A new sn-cn method is used for obtaining traveling wave solutions for this equation with minimal calculations. As a result, abundant new compactons: solitons with the absence of infinite wings, solitary wave and periodic wave solutions of this equation is obtained. The properties of the K(k,n) equations are shown in figures. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Solitary Pattern Solutions; Hamiltonian Amplitude Equation; Korteweg-Devries Equation; Traveling-Wave Solutions; de Vries Equation; Nonlinear Dispersion; N) Equations; Kp Equations; Solitons; Kdv